Moral naturalizada - Ísis Esteves Ruffo (2020)
The present work aims to present and discuss the moral phenomenon from a naturalistic perspective, that is, to offer an explanation of morality that does not resort to supernatural facts or properties or any other metaphysical realm besides the natural one. Therefore, the proposal of ethical naturalism starts from the premise that even a fluid phenomenon such as human morality can be understood in terms of properties, relationships, or facts that appear in scientific descriptions of the world. Over the course of the twentieth century, the naturalistic proposal lost its adherents in confronting the open question argument, an objection that showed that definitions of moral types in natural types are not analytically true. The present metaethical proposal, however, later develops into such difficulty as a new naturalistic possibility. Naturalistic moral neorealism differs from its predecessors in adopting a semantic theory, characteristic of natural kinds, which allows some definitions not to be grasped semantically and thus not to be analytically true. In this case, the definitions offered for moral kinds are synthetically true and must be discovered by empirical rather than conceptual means. Neorealism, however, faces its own difficulties; the first is to show how semantics for natural kinds also apply to moral kinds, which involves constructing a theory that approximates these two kinds that, at least initially, do not appear to be of the same nature. One of the most relevant semantic objections surrounding this supposed dichotomy is formulated in the Moral Twin Earth argument. Moral Twin Earth shows that our intuitions work in different ways when dealing with moral kinds and natural kinds: While we naturally think of natural kinds as rigid designators, the same does not seem to follow in the case of moral kinds, and if naturalistic semantics requires rigid designation, then it is not suitable for moral kinds. There are some replicas of the Moral Twin Earth argument that we will discuss in this text, but the main point not taken into account in semantic criticism is that, as neorealism puts it, moral kinds and not even natural kinds need to be rigid designators to receive naturalized definitions. Moral kinds and a significant portion of natural kinds are functional kinds, that is, kinds that have high compositional plasticity and therefore need not rigidly designate a specific set of properties.